Research on the Seismic Isolation Effect of the Ring Spring–Friction Pendulum Bearing in the Dakai Underground Subway Station - Jie Zhang; Jie Jia (Applied Sciences, 2023)
During strong earthquakes, the vertical seismic force becomes an essential factor affecting shallow underground structures that cannot be ignored. In this situation, it is proposed that ring spring–friction pendulum two-way seismic isolation bearings be set up at the bottom of such structures. Targeting the Dakai underground station and the Kobe earthquake, a soil-structure force model was established based on the damage to the underground structure and dynamic simulation was carried out using Abaqus software. The advantages of the ring spring–friction pendulum bearing over the ring spring bearing alone and the friction pendulum bearing alone were compared. The simulation results showed that the structure displayed a good seismic isolation effect in both horizontal and vertical directions after setting the ring spring–friction pendulum bearing. The deflection in the midspan of the roof reduced to less than 5 cm, the horizontal relative displacement of the structure reduced to less than 3 cm, there was no obvious damage to the structure, the axial pressure ratio of the mid-pillar reduced to less than 0.5, the axial force on the mid-pillar reduced by more than 50%, and the shear force reduced by more than 30%. In addition, by comparing the damage to the structure after setting the annular spring bearing and the friction pendulum bearing, we found that a vertical seismic isolation device is more crucial than a horizontal seismic isolation device for shallow underground structures. Setting a vertical damping device can make the structure retain part of the ductility and reduce the damage to the structure, so the ground vertical seismic mitigation design should be strengthened when a shallow underground structure is designed.